2011
DOI: 10.1002/cbdv.201000225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Antimicrobial Activity of the Leaf and Rhizome Oils of Alpinia pahangensisRidl., an Endemic Wild Ginger from Peninsular Malaysia

Abstract: The essential oils from the leaves and rhizomes of Alpinia pahangensis Ridl., collected from Pahang, Peninsular Malaysia, were obtained by hydrodistillation, and their chemical compositions were determined by GC and GC/MS analyses. The major components of the rhizome oil were γ-selinene (11.60%), β-pinene (10.87%), (E,E)-farnesyl acetate (8.65%), and α-terpineol (6.38%), while those of the leaf oil were β-pinene (39.61%), α-pinene (7.55%), and limonene (4.89%). The investigation of the antimicrobial activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…From our previous study on essential oil of Alpinia pahangensis which also contain γ-selinene and α-terpineol as the major components, showed that the rhizome oil exhibited lower MIC values and the results were comparable to the activity of oxacillin when tested against the same five strains of Staphylococcus aureus used in this study (Awang et al 2011). The major compound, α-terpineol, from rhizomes of A. scabra and A. murdochii in this study has been reported by Li et al (2014) to exhibit strong antibacterial activity against Salmonella enteritidis and Staphylococcus aureus with MIC values of 1.56 and 3.13 µg/mL, respectively.…”
Section: Anti-microbial Activitysupporting
confidence: 64%
“…From our previous study on essential oil of Alpinia pahangensis which also contain γ-selinene and α-terpineol as the major components, showed that the rhizome oil exhibited lower MIC values and the results were comparable to the activity of oxacillin when tested against the same five strains of Staphylococcus aureus used in this study (Awang et al 2011). The major compound, α-terpineol, from rhizomes of A. scabra and A. murdochii in this study has been reported by Li et al (2014) to exhibit strong antibacterial activity against Salmonella enteritidis and Staphylococcus aureus with MIC values of 1.56 and 3.13 µg/mL, respectively.…”
Section: Anti-microbial Activitysupporting
confidence: 64%
“…For instance, oil derived from the overground parts of Mantisalca duriaei Briq. Et Cavill with farnesyl acetate as a dominant compound is characterised by interesting antibacterial activity (Boussaada et al, 2009), likewise the oil from Alpinia pahangensis Ridl rhizome, with farnesyl acetate as a major component as well (Awang et al, 2011). It is necessary underline that in the case the two Arnica spp.…”
Section: Tablementioning
confidence: 99%
“…S. aureus is a common Gram-positive bacterium that can cause pathogenic conditions including food-borne diseases and infections ranging from minor localized skin disturbances to life-threatening deep tissue and systemic illness. Different components of EOs obtained from Alpinia pahangensis , Origanum vulgare , Origanum dictamnus , Mentha piperita , Lavandula hybrida , Zataria multiflora and Hofmeisteria schaffneri have been tested against S. aureus , and all were found to possess potential inhibitory activity [ 30 , 31 ]. Furthermore, combination of essential oil with an antimicrobial agent produces a synergistic effect against multidrug-resistant S. aureus , and in many cases, a substantial decrease in the MIC has been observed [ 32 ].…”
Section: Antimicrobial Activity Of Essential Oilsmentioning
confidence: 99%